Adopt Biodynamic Farming for sustainable agriculture - Aswal, J S; Sha, Binita; Uniyal, D P (Indian Farming, 2017)
Biodynamic farming is seen as an alternate form of agriculture, meant to avoid health hazards caused by increasing use of agrochemicals. It is an advanced, ecofriendly practice based on principles of soil biotechnology and microbiology.